Assessing CO2 emissions of electric vehicles in Germany in 2030. (August 2015) - Jochem, Patrick; Babrowski, Sonja; Fichtner, Wolf
Highlights: Comparison of four assessment approaches for CO2 emissions from electric vehicles. Calculation of CO2 emissions from electric vehicles for Germany in 2030. CO2 emissions vary depending on the way they are assessed. Controlled charging might help to cut CO2 emissions. Design policy instruments to promote EVs with extremely low CO2 emissions! Abstract: Electric vehicles are often said to reduce carbon dioxide (CO2 ) emissions. However, the results of current comparisons with conventional vehicles are not always in favor of electric vehicles. We outline that this is not only due to the different assumptions in the time of charging and the country-specific electricity generation mix, but also due to the applied assessment method. We, therefore, discuss four assessment methods (average annual electricity mix, average time-dependent electricity mix, marginal electricity mix, and balancing zero emissions) and analyze the corresponding CO2 emissions for Germany in 2030 using an optimizing energy system model (PERSEUS-NET-TS). Furthermore, we distinguish between an uncontrolled (i.e. direct) charging and an optimized controlled charging strategy. For Germany, the different assessment methods lead to substantial discrepancies in CO2 emissions for 2030 ranging from no emissions to about 0.55 kg/kWhel (110 g/km). These emissions partly exceed the emissions from internal combustion engine vehicles. Furthermore, depending on the underlying power plant portfolio and the controlling objective, controlled charging might help to reduce CO2 emissions and relieve the electricity grid. We therefore recommend to support controlled charging, to develop consistent methodologies to address key factors affecting CO2 emissions by electric vehicles, and to implement efficient policy instruments which guarantee emission free mobility with electric vehicles agreed upon by researchers and policy makers.